2019
DOI: 10.1183/20734735.0346-2018
|View full text |Cite
|
Sign up to set email alerts
|

Under- and over-diagnosis of COPD: a global perspective

Abstract: Globally, chronic obstructive pulmonary disease (COPD) is the fourth major cause of mortality and morbidity and projected to rise to third within a decade as our efforts to prevent, identify, diagnose and treat patients at a global population level have been insufficient. The European Respiratory Society and American Thoracic Society, along with the Global Initiative for Chronic Obstructive Lung Disease (GOLD) strategy document, have highlighted key pathological risk factors and suggested clinical treatment st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
100
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(121 citation statements)
references
References 81 publications
(110 reference statements)
6
100
0
1
Order By: Relevance
“…In spite of increased use of spirometry in primary care, COPD is still an underdiagnosed disease. 35 Although availability of spirometers, the application of the instrument varies greatly between practices. 34 To promote a further drop in smoking prevalence among subjects with COPD, improved identification of the disease should be given high priority.…”
Section: Implications For Clinical Practicementioning
confidence: 99%
“…In spite of increased use of spirometry in primary care, COPD is still an underdiagnosed disease. 35 Although availability of spirometers, the application of the instrument varies greatly between practices. 34 To promote a further drop in smoking prevalence among subjects with COPD, improved identification of the disease should be given high priority.…”
Section: Implications For Clinical Practicementioning
confidence: 99%
“…Chronic obstructive pulmonary disease (COPD) is an exemplar of a condition in which there are concerns that limited awareness of guideline recommendations amongst general practitioners (GPs) [6,7] leads to misdiagnosis and inappropriate management [8,9]. COPD affects an estimated 251 million people worldwide [10] and globally, is predicted to be the third leading cause of death by 2030 [11].…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with COPD are at an increased risk of developing lung tumors and other conditions, such as emphysema and chronic bronchitis (13). COPD is a risk factor for SCC and the association between the two remains unclear (13). Therefore, the association between COPD and SCC needed to be elucidated the present study identified marker genes uniquely associated with SCC with COPD.…”
Section: Discussionmentioning
confidence: 84%
“…Symptoms include trouble with breathing, coughing, mucus (sputum) generation and wheezing (12). This is caused by exposure to irritant compounds or particulate matter, predominantly from tobacco smoke (13). Individuals with COPD are at an increased risk of developing lung tumors and other conditions, such as emphysema and chronic bronchitis (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation